Implementasi Nilai-Nilai Islam sebagai Rekonstruksi Generasi Berkarakter - Muhammad Nuzuli; Rahma Yulia Putri; Ilian Ikhsan (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2025)
The application of Islamic values ​​to character education to build a generation with noble character focuses on several important issues. First, there are difficulties in integrating Islamic values ​​in depth into an already busy curriculum, thereby limiting time and space for character education. This often happens. This research uses a library research approach. The main data sources for this research include scientific journal articles and related research reports. According to research, the first form of applying Islamic values ​​to character education in order to build a generation with noble character is through incorporating Islamic values ​​into the curriculum and through daily activities such as prayer and reading the Koran. The role of the teacher as a role model Values ​​such as honesty, responsibility and compassion are instilled in shaping students' character. Second, the application of Islamic values ​​in character education is urgently needed to build a generation with noble morals. In the midst of the influence of modernization, the application of Islamic values ​​will lead to the formation of strong, important morals. These values ​​help students build a strong moral and social identity, thereby supporting their positive contribution to society. Third, the challenges of implementing Islamic values ​​in character education to build a generation with noble character include diverse student backgrounds, limited curriculum and resources, as well as external influences such as the media and the environment. Overcoming these obstacles and maintaining the integrity of Islamic character education requires the cooperation of schools, families and communities.